Complex aortic valve repair in congenital patients: clinical feedback - Barbier, Marie-Anne; Bulescu, Nicolae Cristian; Metton, Olivier; Bou Karam, Lea; Martin Bonnet, Caroline; Moulin Zinsch, Anne; Lilot, Marc; Henaine, Roland (Frontiers in Pediatrics, 2024)
In patients with congenital aortic valve disease, particularly in young adults, the best strategy for aortic valve surgery has not been clearly established. This study investigates the mortality, perioperative morbidity and echocardiographic evolution of complex aortic valve repair techniques. Material and methods: We performed a retrospective monocentric descriptive study of patients operated at the Louis Pradel Hospital (Lyon) from 2017 to 2023. We included patients operated for complex aortic valve repair by the congenital heart surgery team, excluding simple commissurotomies. The primary endpoint was postoperative survival. The secondary endpoints were freedom from surgical reintervention and echocardiographic evolution of aortic regurgitation, aortic stenosis and annular diameter. The analysis was performed using Kaplan Meier methods. Results: Twenty-eight patients were included. The mean age was 11,1 years (range 1 -35 years) and the mean weight was 37,5 kg (range 8,2 -79 kg). The postoperative survival rate was 96.4% at discharge (27/28 patients). The mean follow-up interval was 35 months (range 14-79 months). At the end of the follow-up, the freedom from reoperation was 85,7%. Four patients underwent reoperation for worsening aortic valve and/or ventricular function (1 heart transplantation, 2 Ross procedures, 1 aortic valve replacement). Results on secondary endpoints showed a trend towards improvement in annular diameter postoperatively between pre-and postoperative echocardiography for each patient, with no statistically significant difference for aortic insufficiency, but for aortic stenosis (p=0,02).This study shows an excellent survival rate, and a similar risk of reintervention compared with literature data. All the data described above argue in favor of an aortic valve repair surgery as a first line procedure in case of congenital heart disease.